Cross-layer design of partial spectrum sharing for two licensed networks using cognitive radios - Jiang, X; Wong, K; Zhang, Y; Edwards, D (Wiley, 2015)
To utilize spectrum resources more efficiently, dynamic spectrum access attempts to allocate the spectrum to users in an intelligent manner. Uncoordinated sharing with cognitive radio (CR) users is a promising approach for dynamic spectrum access. In the uncoordinated sharing model, CR is an enabling technology that allows the unlicensed or secondary users to opportunistically access the licensed spectrum bands (belonging to the so-called primary users), without any modifications or updates for the licensed systems. However, because of the limited resources for making spectrum observations, spectrum sensing for CR is bound to have errors and will degrade the grade-of-service performance of both primary and secondary users. In this paper, we first propose a new partial spectrum sharing policy, which achieves efficient spectrum sharing between two licensed networks. Then, a Markov chain model is devised to analyze the proposed policy considering the effects of sensing errors. We also construct a cross-layer design framework, in which the parameters of spectrum sharing policy at the multiple-access control layer and the spectrum sensing parameters at the physical layer are simultaneously coordinated to maximize the overall throughput of the networks, while satisfying the grade-of-service constraints of the users. Numerical results show that the proposed spectrum sharing policy and the cross-layer design strategy achieve a much higher overall throughput for the two networks. © 2013 John Wiley and Sons, Ltd.